ASUHAN KEBIDANAN IBU BERSALIN DENGAN ATONIA UTERI PADA NY. “H” DI BPM BD. HJ. OOM ROCHMULYATI, S.ST TAHUN 2019 - Qonita; Nadya Rahmah (Poltekkes 'Aisyiyah Banten, 2019)
According to the Indonesia Demographic Health Survey (SDKI) (2015), said that the Maternal Mortality Rate (MMR) in Indonesia reached 305 per 100,000 live births. Based on data from the Health and Information Center of the Ministry of Health (2015) the causes of maternal death are bleeding (30.3%), hypertension (28.8%), and pregnant women with anemia (37.1%). One cause of maternal death is bleeding. The cause of bleeding that needs serious attention is Atonia Uteri, because if the handling is late it will worsen the situation and can threaten the life of the mother. The incidence of uterine atony is around 1-3% of all deliveries. The purpose of this case study is to be able to carry out maternity care with Atonia Uteri in Ny.